Nurturing Young Muslim Students as Part of Minority Group in American Society - Dellarosa, Maretha; Windarto, Titus Eko (Muslim Education Review, 2024)
Placing a religious foundation in the early generation presents challenges for Muslims, especially when religion is not part of academic curricula. Even though there has been debates on religious teaching, the significance of infusing religious values remains unquestionable in students’ lives. Those who need to deepen their religious faith enroll in religious classes outside school activities. The present article sets out to examine two Muslim teachers’ efforts to nurture young Muslims’ identity and the challenges they encounter. In doing so, this study employs the Early Years Foundation Stage (EYFS) and identity theory as theoretical frameworks. The findings of this qualitative study add to the literature on the importance of nurturing Muslim students’ identity in a non-Muslim country, the U.S. This is important because the ongoing hate against Islam in a post-9/11 world causes Muslim and Muslim-looking students to face religious discrimination on academic grounds. We argue that infusing Islamic values to young Muslim students serves as a strong foundation for students’ spiritual development.